Markers of early biological effects after exposure to cytotoxic chemotherapeutic agents in the workplace - Tiangco, Beatrice Y.
Introduction: It is unclear whether exposure to chemotherapeutic agents in the workplace increases the risk for the development of cancer. Mutations in non-disease related "reporter" genes like the hypoxanthine guanine phosphoribosyl transferase (HPRT) gene provide information regarding primary mutation frequencies, and subsequently, carcinogenicity. These mutations are of considerable value for monitoring human populations for potential health hazards due to environmental mutagens and carcinogens. Objective: To explore the exposure to cytotoxic chemotherapeutic agents as a factor in the development of early biologic markers of carcinogenesis. To assess the mutation frequency in lymphocytes using HPRT assay of tertiary oncology clinic health care workers with different degrees of exposure to cytotoxic chemotherapy and to explore if there is an association between these two variables. Study Design: Exploratory cross-sectional analytical study. Setting: UP-PGH Medical Center Cancer Institute (tertiary setting). Subject and Exposure of Interest: Health workers of UP-PGH assigned to the Cancer Institute were recruited. Sample Size: Preliminary 41 out of 169 (0.2 correlation coefficient, =0.05, = 20% Outcome Measurement: Peripheral blood from each subject was assayed using a standardized protocol for the presence of HPRT mutations. A questionnaire on the subject's age, sex, history of exposure to cytotoxic chemotherapy, illnesses, medications, family history of cancer, smoking habit, diet, alcohol intake, was used to collect pertinent data.